Camptothecin-producing endophytic bacteria from pyrenacantha volubilis hook. (Icacinaceae): a possible role of a plasmid in the production of camptothecin - Soujanya, K. N.; Siva, R.; Kumara, P. Mohana; Srimany, Amitava; Ravikanth, G.; Mulani, F. A.; Aarthy, T.; Thulasiram, H. V.; Santhoshkumar, T. R.; Nataraja, Karaba N.; Shaanker, R. Uma (Phytomedicine, 2017)
Background: Camptothecin (CPT), a quinoline alkaloid, is a potent inhibitor of eukaryotic topoisomerase I. Because of this property, several derivatives of CPT are used as chemotherapeutic agents. CPT is produced by several plant species belonging to the Asterid clade as well as by a number of endophytic fungal associates of these plants. In this study, we report the production of CPT by four bacterial endophytes and show the possible role of a plasmid in the biosynthesis of CPT. Methods: Endophytic bacteria were isolated from leaves, stems and fruits of Pyrenacantha volubilis Hook. (Icacinanceae). The bacterial isolates were purified and analyzed for production of CPT by ESI-MS/MS and NMR analysis. Bacterial identity was established based on the morphology and 16s rRNA sequence analysis. Crude extracts of the bacterial endophytes were evaluated for their cytotoxicity using colon cancer cell lines. The role of plasmid in the production of CPT was studied by purging the plasmid, using acriflavine, as well as reconstituting the bacteria with the plasmid. Results: Four bacterial isolates, Bacillus sp. (KP125955 and KP125956), Bacillus subtilis (KY741853) and Bacillus amyloliquefaciens (KY741854) were found to produce CPT in culture. Both based on ESI-MS/MS and NMR analysis, the identity of CPT was found to be similar to that produced by the host plant. The CPT was biologically active as evident by its cytotoxicity against colon cancer cell line. The production of CPT by the endophyte (Bacillus subtilis, KY741853) attenuated with sub-culture. A likely role of a plasmid in the production of CPT was established. A 5 kbp plasmid was recovered from the bacteria. Bacterial isolate cured of plasmid failed to produce CPT. Conclusion: Our study implies a possible role of a plasmid in the production of CPT by the endophytic bacteria and opens up further work to unravel the exact mechanisms that might be involved.